KAJIAN SUHU DAN LAMA PENGERINGAN TERHADAP KUALITAS ORGANOLEPTIK TEH HERBAL ROSELLA (Hibiscus sabdariffa Linn) - Evi Sribudiani; A.K. Parlindungan; Volliadi ' (Universitas Riau, 2011)
Rosella plants (Hibiscus sabdariffa Linn) is a source of very complex chemicalcomponents, especially in the petals. In addition, rosella flower petals is also one commodityeasily damaged, because the rosella flower petals have a fairly high water content of 86.2%.Therefore it is necessary for handling the effort to prevent such damage on dried rosella flowerpetals. The purpose of this study to look at the effects of temperature and duration of differentdrying of the organoleptic quality of herbal tea rosella (Hibiscus sabdariffa Linn.) The results ofthis study indicate that differences in temperature and drying time significantly influenced theresulting water content. The best treatment is A4 (drying at a temperature of 950C with a timeof drying for 3 hours) with a water content of 6.528%. In the organoleptic test 3.61 panelists forcolor, aroma of 3.05, and a sense of 3.22. Overall assessment of the A1-A4 shows the treatmentreceived by the panelists.Key words: rosella, drying temperature, drying time